2021
DOI: 10.21203/rs.3.rs-250110/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the Mechanism of Laminaria for the Treatment of Alzheimer's Disease based on Network Pharmacology

Abstract: Background:Laminaria japonica has also been reported to have a therapeutic effect on AD, but the mechanism is not entirely clear. To explore the mechanism of Laminaria for the treatment of Alzheimer's disease (AD), the “active components-targets” network and the protein-protein interaction (PPI) network were constructed for analyzing targets’ functions and pathways. Methods:The main active components of Laminaria were extracted using the TCMSP database and were predicted and screened by GeneCards. Cytoscape wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(28 reference statements)
0
0
0
Order By: Relevance
“…In recent years, a large number of studies have been conducted on the mechanism of action of acupuncture in the treatment of Parkinson's disease, and many experimental evidences have shown that acupuncture can affect dopamine neurons, produce anti-excitotoxic effects, improve oxidative stress, regulate immune abnormalities, and modulate mitochondrial dysfunction to alleviate Parkinson's disease symptoms. And in this paper cAMP signaling pathway, IL-17 signaling pathway and dopaminergic synapse is consistent with the literature, suggesting that acupuncture for Parkinson's disease may be effective by activating the cAMP signaling pathway, IL -17 signaling pathway and dopaminergic synapse [21,22]. Further validation through experiments is required for follow-up.…”
Section: Discussionsupporting
confidence: 85%
“…In recent years, a large number of studies have been conducted on the mechanism of action of acupuncture in the treatment of Parkinson's disease, and many experimental evidences have shown that acupuncture can affect dopamine neurons, produce anti-excitotoxic effects, improve oxidative stress, regulate immune abnormalities, and modulate mitochondrial dysfunction to alleviate Parkinson's disease symptoms. And in this paper cAMP signaling pathway, IL-17 signaling pathway and dopaminergic synapse is consistent with the literature, suggesting that acupuncture for Parkinson's disease may be effective by activating the cAMP signaling pathway, IL -17 signaling pathway and dopaminergic synapse [21,22]. Further validation through experiments is required for follow-up.…”
Section: Discussionsupporting
confidence: 85%